ANALISIS MODEL MATEMATIKA PENYEBARAN ASAP PADA KEBAKARAN RUMAH - Rahman, Mohammad Fadli; Fatahillah, Arif; Dafik, D; Kristiana, Arika Indah (Department of Mathematics Education , University of Jember, 2014)
Abstract. The house fire will produce smoke and hot gas. When we are trapped inside the house fire, we need a secured evacuation path to escape. In this research talk about mathematical model analysis on the spread of house fire by using a finite volume method. Researcher will study the simulation of smoke and hot gas by utilising a mathematical model. We will also model the spread of hot smoke equations based on momentum and energy models. We used Matlab to analyse the spread of smoke and hot gas and use Fluent software to have a graphic animation. The result of simulation with Matlab and Fluent are chart, tables, and images spread of smoke and hot gas. The result shows that te spread of the smoke and hot gas depends on the epicentrum of fire. Key Words: finite volume method, house fire, mathematical model